2022
DOI: 10.4149/gpb_2022010
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic exercise ameliorates myocardial ischemia/reperfusion injury and thrombosis of diabetic rats via activation of AMPK/Sirt1/PGC-1α pathway

Abstract: This current work is aimed to make investigations for the action mechanism of aerobic exercise in rats with type 2 diabetes mellitus (T2DM) after myocardial ischemia/reperfusion injury (MI/RI). The high-fat diet was used to induce T2DM in male Wistar rats. After treatments, the rats in the exercise groups were underwent swimming training for 8 weeks. Two days later, all the rats were subjected to perform MI/RI experiments via left anterior descending artery ligation and reperfusion. The blood samples and myoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…These results are sufficient to show that AT promotes cardioprotection and inhibits ERS after MI at least partially through PCAF. Although the mechanism through which AT regulates PCAF is unknown, PCAF interacts with multiple members of the sirtuin deacetylase family 46,47 that are regulated by AT and exert cardioprotective effects in mice with myocardial ischemia, [48][49][50] which may be one of the mechanisms through which PCAF functions. However, the specific mechanism by which AT regulates PCAF and how PCAF affects cardiac remodeling must be further explored in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…These results are sufficient to show that AT promotes cardioprotection and inhibits ERS after MI at least partially through PCAF. Although the mechanism through which AT regulates PCAF is unknown, PCAF interacts with multiple members of the sirtuin deacetylase family 46,47 that are regulated by AT and exert cardioprotective effects in mice with myocardial ischemia, [48][49][50] which may be one of the mechanisms through which PCAF functions. However, the specific mechanism by which AT regulates PCAF and how PCAF affects cardiac remodeling must be further explored in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of expression of muscle factor irisin during exercise (treadmill exercise, swimming and sprint training) activates the AMPK signaling pathway [ 51 ]. A previous study has shown that regular exercise activates the AMPK/Sirtuin-1 (SIRT1) pathway, which in turn regulates downstream PGC-1α [ 52 ]. Many other studies have found that exercise delays cognitive decline primarily through the PGC-1α–FNDC5–BDNF signaling pathway in the AD hippocampus [ 53 55 ].…”
Section: Methodsmentioning
confidence: 99%
“…It also decreased myocardial injury markers and inflammation responses. The study suggests that aerobic exercise can reduce myocardial ischemia/reperfusion injury and repress thrombosis by activating the AMPK/SIRT1/PGC-1α pathway in rats with T2DM ( Wang, 2022 ). Furthermore, SIRT1 plays a key role in suppressing PPAR-𝛾 in mature adipocytes, decreasing fat accumulation.…”
Section: Sirt1 and Inflammationmentioning
confidence: 98%